1998
DOI: 10.1136/bmj.317.7162.856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex of fetus on asthma during pregnancy: blind prospective study

Abstract: (Accepted 11 June 1998)Effect of sex of fetus on asthma during pregnancy: blind prospective studyThe course of asthma during pregnancy is variable and may remain unchanged, worsen, or improve, returning to the pre-pregnancy state within three months after parturition.1 Some patients experience the same changes in each pregnancy, but nearly half do not, suggesting some intrinsic or extrinsic factor unique to each pregnancy such as the sex of the fetus. 1 We observed that the condition of patients with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 6 publications
1
29
1
Order By: Relevance
“…Together, these data indicate that the adverse perinatal outcomes observed in the current cohort are not specific to the most severe cases (including asthma exacerbations) of asthma. Despite evidence indicating that females carrying a female fetus experience a deterioration of asthma symptoms, as well as an increased requirement for medication and increased circulating monocytes in pregnancy [28,[46][47][48][49], most previous studies failed to consider the sex of the infant in their analyses. In the current study, a sex-specific association was demonstrated, with the risk of SGA increased in male but not female neonates in pregnancies of females with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data indicate that the adverse perinatal outcomes observed in the current cohort are not specific to the most severe cases (including asthma exacerbations) of asthma. Despite evidence indicating that females carrying a female fetus experience a deterioration of asthma symptoms, as well as an increased requirement for medication and increased circulating monocytes in pregnancy [28,[46][47][48][49], most previous studies failed to consider the sex of the infant in their analyses. In the current study, a sex-specific association was demonstrated, with the risk of SGA increased in male but not female neonates in pregnancies of females with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The sex of the fetus may be one factor contributing to worsening asthma during pregnancy. A number of recent studies have reported that the presence of a female fetus is associated with worsening maternal asthma and increased requirement for inhaled steroid treatment (Dodds et al 1999;Beecroft et al 1998;Murphy et al 2003). Murphy et al (2003) have reported that circulating monocyte concentrations increase in asthmatic women who avoid the use of inhaled glucocorticoids during pregnancy and are pregnant with a female fetus.…”
Section: Effect Of Asthma During Pregnancy On Maternal Health and Fetmentioning
confidence: 98%
“…In a blind prospective study, BEECROFT et al [99] studied 34 pregnant mothers with moderate or severe asthma who were using regular treatments. Significantly more mothers pregnant with a female foetus reported shortness of breath, nocturnal waking and a worsening of cough and asthma in general, while mothers pregnant with a male foetus were more likely to report an improvement in asthma [99].…”
Section: The Effect Of Pregnancy On Asthmamentioning
confidence: 99%
“…In a blind prospective study, BEECROFT et al [99] studied 34 pregnant mothers with moderate or severe asthma who were using regular treatments. Significantly more mothers pregnant with a female foetus reported shortness of breath, nocturnal waking and a worsening of cough and asthma in general, while mothers pregnant with a male foetus were more likely to report an improvement in asthma [99]. DODDS et al [103] reported that re-analysis of their Canadian population-based study indicated that fewer asthmatic subjects pregnant with a male foetus required steroids for treatment (14%), compared with asthmatic subjects pregnant with a female foetus (20%) [1].…”
Section: The Effect Of Pregnancy On Asthmamentioning
confidence: 99%